Efficacy of music therapy on stress and anxiety prior to dental treatment: a systematic review and meta-analysis of randomized clinical trials - López-Valverde, Nansi; López-Valverde, Antonio; Macedo de Sousa, Bruno; Blanco Rueda, José Antonio (Frontiers in Psychiatry, 2024)
Introduction Stress and anxiety are emotional states that often accompany patients who have to receive dental treatments, leading them to postpone or avoid treatments with the consequent deterioration of their oral health and, hence, their general condition. Music therapy has been shown to be an alternative to other treatments that are invasive and not without danger, such as anxiolytics or sedation. This systematic review and meta-analysis evaluated the effect of music therapy on anxiety and stress prior to dental treatments. Methods Studies published in PubMed (through Medline), Web of Science (WOS), Embase, and Cochrane Library databases were consulted up to October 2023. The inclusion criteria were established for intervention studies (randomized controlled trials, RCTs) according to the PICOS (population, intervention, comparison, outcomes, and study) strategy in subjects with dental stress and anxiety (participants) treated with music therapy (intervention) in comparison with patients without music therapy (control) and evaluating the response to treatment (outcomes). Results A total of 154 results were obtained, with 14 studies finally selected. The risk of bias and the methodological quality were assessed using the Cochrane Risk of Bias Tool and the Jadad scale, respectively. A random-effects meta-analysis was used to quantify the results of the pooled studies, while a fixed-effects meta-analysis was used for studies in the pediatric population. The meta-analysis of pooled studies found statistical significance in the subgroups of anxiety and anxiety–stress (p = 0.03 and p = 0.05, respectively), with an overall effect in favor of the intervention group (p = 0.005). Meta-analysis of the studies in the pediatric population showed considerable statistical significance for the experimental group (p < 0.00001). Conclusion Music therapy as a treatment for stress and anxiety, prior to dental treatment, proved to be effective in both children and adults although more well-designed randomized clinical studies are needed to validate its efficacy. Systematic review registration INPLASY, identifier 202312000.